Multimodal Discourse Analysis Of Gay Identity In Lil Nas X ‘Montero (Call Me By Your Name)’ Music Video: Implications In Religion - Mutiara, Mutiara; Tambunan, Friska; Purba, Thesia Aprianti; Tamba, Elizabeth Rusida Yosephine; Zein, T. Thyrhaya (Innovative: Journal Of Social Science Research, 2024)
Call Me by Your Name (Montero) by Lil Nas X is a song that portrays the breaking of social norms, particularly regarding sexuality. This research aims to analyze gay identity in the song and its implications in religion. The researchers use descriptive qualitative method and multimodal approach to analyze the song. The analysis uses Theo Van Leeuwen theory to analyze the visual, linguistic, auditory, intertextuality, and contextual factors. The result of this research is Lil Nas X reclaims religious symbols, transforming them from means of oppression into acts of personal emancipation. Based on analysis, the conclusion of Lil Nas X's “Call Me by Your Name” is a strong expression of self-acceptance, resistance to society and religious condemnation, and a celebration of LGBTQ+ identity, especially gay since Lil Nas himself is a gay.